A comparabilidade de escalas para a atribuição de pesos em exames de seleção - de Melo Barroso, Camen Lucia (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
When composite scores are used to select individuals, the effective weight of each component variable of these scores is defined in terms o f the contribution o f the variable to the variance of the composite. The objective of this paper is to demonstrate formally that the effective weight of a variable depends on the nominal weight deliberately attributed to it as well as on the variance of that variable and its covariance with each of the remaining variables. One might reasonably suppose that in many situations the covariance of each variable with each of the remaining variables will not differ greatly. The need, therefore, arises for the use of standardized scales, with equal variances, so that the influence of each variable might be effectively determined by the weight deliberately attributed to it. Specific examples involving the selection of university students are given for illustrative purposes.